MENU “TUTO” TEPUNG SAGU Arenga microcarpa SEBAGAI MP-ASI PERTAMA TERHADAP STATUS GIZI BAYI DI KABUPATEN KEPULAUAN SANGIHE - Phembriah S. Kereh; Meildy E. Pascoal; Yohanis A. Tomastola (Jurnal GIZIDO, 2016)
Toddlers ages 0-24 months at a time of rapid growth and development, so it is often termedas the golden period once the critical period. Golden period can be realized if at this timeinfants and children receive appropriate nutrition for optimal growth and development. SagoBaruk (arenga microcarpa) has long been used by the inhabitants of the region of the DistrictSangihe, Talaud and Sitaro, as a main meal and specifically during more specific baby 0-11months while the child is first given complementary foods breast milk (MP-ASI ) TUTO menumade from raw materials sago types arenga microcarpa or known by local names that SEHOtree or palm tree or palm wine-producing trees.This type of research is the study of experimental use quasy Experiment design of this studywill be carried out in some areas health centers in Sangihe Islands Regency in April s / dDecember 2015. The sample size in this study is determined by the formula Estimating thedifference between two population proportion each each group of 50 infantsThe study provides an overview among other subjects in this study is a child under twoyears. The mean age of the subjects in this study was 9.5 months lows age of 3 months and22-month highs. The mean birth weight (BBL) subjects in this study was 3 kg of low birthweight 2 kg and 3.8 kg, while the highest average length of 47.72 cm birth weight is thelowest 45 cm and 51 cm high. The mean value of z score nutritional status (BB / U) childrenbefore intervention was -0.39 SD (normal category) z score lowest score was -2.91(malnutrition) and the highest was 1.92 (normal) while the average value of z score childrenafter the intervention is -0.27 -2.81 SD SD is the lowest and the highest was 1.91, while theSD indicator of nutritional status of TB / U before and after there was no change in categoryfor measurement before and after the intervention of grace time is only 7 days when seen ofthe frequency distribution it is seen that of 50 children 5 people (10%) of them have thestatus of malnutrition but jka seen from the indicators of TB / U the 50 children 3 people (6%)were classified as very short and 3orang (6%) relatively short , The results of the analysis oftwo different groups of pairs using Paired sample T Test shows that there are differences inboth weight and nutritional status of the subjects in this study (p <0.01). The results of theanalysis of post hock (Wilcoxon) shows that of the 50 subjects 47 people among them anincrease in body weight between 0.3-0.8 kg and the value of z score indicates nutritionalstatus nutritional status differences before and after intervention of 0.2 SD rising close to themedian ,Conclusion penelitiaan This is a menu tuto modified with a protein from the tuna can be usedas an alternative to breast milk because it can meet the nutritional needs of children,according to figures the recommended dietary allowance (RDA) and can increase the child'sweight and can further improve the nutritional status child.